Expression of Simian Virus 40 Large T-Antigen: A Case Control Study of Non-Hodgkin Lymphoma - Dinantia, Nugira; Anggorowati, Nungki (Asian Pacific Journal of Cancer Biology, 2021)
Background: Cancer such as neoplasma lymphoma is related to the immune system. Of all lymphoma cases, about 90% are Non-Hodgkin Lymphoma (NHL). In the United Kingdom, NHL is among the five most frequently diagnosed cancer cases. In Indonesia, based on statistical data from the Dharmais Cancer Center Hospital in 2006, NHL was in the ten most commonly diagnosed cancers. The global incidence of NHL continues to increase annually in western countries, especially in Caucasian populations, men and the elderly. The etiology of NHL is uncertain. Viral infection is thought to be associated with the pathogenesis of NHL. One of them is the Simian 40 virus (SV 40) infection. In some studies, positive SV40 sequencing was found in the majority of NHL cases, but other research found no significant relationship between SV40 infection and NHL. Objective: This study aimed to identify the frequency of SV40 infection in NHL cases in Yogyakarta and to determine the relationship between SV40 infection in NHL cases and clinical patients. Methods: This study examined 102 samples of paraffin blocks from subjects diagnosed with NHL in the Anatomical Pathology Laboratory of Dr. Sardjito Hospital from 2014 through 2016. DNA extraction was done and the results were used for PCR. SV40 genome primer sets were used for the PCR process to identify any positive cases. Results: In this study, all 102 subjects did not indicate genomic L-Tag positive cases of NHL. Conclusion: It cannot be proved that SV40 has a role in the pathogenesis of NHL in Indonesia.